Factors Affecting the Starch Extraction from Jackfruit Seed (Artocarpus heterophyllus L.) - Lien, Duong Thi Phuong; Nhieu, Ly Hua; My, Nguyen Thi Thanh; Que, Phan Thi Thanh (International Journal of Membrane Science and Technology, 2023)
The study was conducted to investigate some factors affecting the starch extraction from jackfruit seeds (JS), including: Jackfruit seed drying temperature, extraction time and ratio of water to jackfruit seed flour (JSF). The JS were dried at various temperatures (50, 60 and 70oC) before grinding into flour. Starch was extracted in 4 levels of time (5, 6, 7 and 8 hours) interacted with 4 ratios of water to JSF (10, 15, 20 and 25 times, v/w). The efficiency of the extraction process was evaluated through the yield and the physicochemical properties of JSS, such as starch content, the color (L value and browning index - BI), water absorption index (WAI), water solubility index (WSI) and swelling power (SP); the scanning electron microscopy (SEM) and the average particle diameter (APD). The drying temperature of 60oC is considered suitable for obtaining good flour for performing starch extraction. Starch extraction from the JSF was carried out with the ratio of water to JSF of 15 times (v/w) for 6 hours at ambient temperature. The yield was 44.96?0.29%; the starch content was 92.06?0.48%. The JSS exhibited the values of WAI, WSI and SP in range of from other starches. The APD of JSS is 6.90–8.50 µm and is classified as small granules. All physicochemical properties as well as the APD of JSS were interrelated. These results showed that the extraction is high yield. The extracted JSS has high starch content and suitable physicochemical properties. When purified effectively, it has the potential to become food or effective complementary ingredients in the development of functional food products.